ENVIRONMENTAL ACTIVISM IN ADAMU’S THE DEATH OF ETERNITY, THE LONE PIPER AND THE BIRD’S CASE AND EKWO’S THE FALL OF SILENCE: IMPLICATIONS FOR THE ERA OF COVID-19 - Alyebo , Nelson O.; Ogba, Victoria Omaji (International Journal of Arts, Languages, Linguistics and Literary Studies, 2023)
It is now common knowledge that man in his efforts to improve the standard of living for humanity, the natural world has continuously been put to danger of global warming, pollution of water, land and air, ozone layer depletion and climate change etc; resulting from industrial and exploration activities, as well as scientific, technological and medical advancements. This paper examines the ways in which writers have highlighted the importance of a safe and pristine environment to mankind. It also focuses on how writers have raised advocacy against human activities which have negative impact on the well-being of the natural environment and by extension, how they literally engage their main characters in active roles necessary to challenge or contend against the structures aiding ecological damage. To achieve these, Adamu’s The Death of Eternity, The Lone Piper and the Bird’s Case and Ekwo’s The Fall of Silence are selected for analysis using ecocritical framework. Data for analysis are excerpts drawn from the same texts. The findings reveal that environmental preservation is only possible through sensitization by which the people would be stirred not only to protect their environment, but also to rise and fight for their rights, seeing that a healthy environment is people’s right without which their potential cannot be realized. The findings also reveal that, consciousness and advocacy are being raised against environmental degradation and ecological devastation. These activities are plunging people’s lives into socio-economic and health problems. Therefore, being ecologically conscious would also help to motivate the reader to take proactive steps against any activities which threaten the peaceful coexistence between man and his environment. The paper concludes that human comfort and wellness depend on the comfort and well-being of his environment. When the environment is polluted and devastated, the lives of the people will definitely be endangered. This is so because there is a symbiotic relationship between man and his environment which makes it difficult to separate one from the influence of the other. Finally, the paper notes that Covid-19 pandemic also has its attendant adverse implications on the environment as the dead are buried within the environment without environmental impact assessment reports; thus adding to the risk factors in the environment.